Cost-consequence analysis of "washing without water" for nursing home residents: A cluster randomized trial. Issue 1 (January 2015) - Schoonhoven, Lisette; van Gaal, Betsie G.I.; Teerenstra, Steven; Adang, Eddy; van der Vleuten, Carine; van Achterberg, Theo
Abstract Background No-rinse disposable wash gloves are increasingly implemented in health care to replace traditional soap and water bed baths without proper evaluation of (cost) effectiveness. Objectives To compare bed baths for effects on skin integrity and resistance against bathing and costs. Design Cluster randomized trial. Setting Fifty six nursing home wards in the Netherlands. Participants: Five hundred adult care-dependent residents and 275 nurses from nursing home wards. Methods The experimental condition 'washing without water' consists of a bed bath with disposable wash gloves made of non-woven waffled fibers, saturated with a no-rinse, quickly vaporizing skin cleaning and caring lotion. The control condition is a traditional bed bath using soap, water, washcloths and towels. Both conditions were continued for 6 weeks. Outcome measures were prevalence of skin damage distinguished in two levels of severity: any skin abnormality/lesion and significant skin lesions. Additional outcomes: resistance during bed baths, costs. Results Any skin abnormalities/lesions over time decreased slightly in the experimental group, and increased slightly in the control group, resulting in 72.7% vs 77.6% of residents having any skin abnormalities/lesions after 6 weeks, respectively (p = 0.04). There were no differences in significant skin lesions or resistance after 6 weeks. Mean costs for bed baths during 6 weeks per resident were estimated at €218.30 (95%CI 150.52–286.08) in the experimental group and €232.20 (95%CI: 203.80–260.60) in the control group (difference €13.90 (95%CI: −25.61–53.42). Conclusion Washing without water mildly protects from skin abnormalities/lesions, costs for preparing and performing bed baths do not differ from costs for traditional bed bathing. Thus, washing without water can be considered the more efficient alternative.